2011
DOI: 10.1016/j.healthplace.2011.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Do physical activity facilities near schools affect physical activity in high school girls?

Abstract: Objective-To investigate associations between the number of physical activity facilities within walking distance of school and physical activity behavior in 12 th grade girls during after-school hours.Methods-Girls (N=1394) from 22 schools completed a self-report to determine physical activity after 3:00 pm. The number of physical activity facilities within a 0.75-mile buffer of the school was counted with a Geographic Information System. Associations between the number of facilities and girls' physical activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 30 publications
0
11
0
2
Order By: Relevance
“…School Proximity to Other PA Facilities: In a study of adolescent girls, school proximity to recreation facilities was associated with PA [ 114 ]. Another study, focused on 12 th graders, found that those who attended schools with five or more physical activity facilities within a 0.75 mile buffer zone around the school were more physically active than those attending schools with fewer than 5 nearby physical activity facilities [ 115 ].…”
Section: Resultsmentioning
confidence: 99%
“…School Proximity to Other PA Facilities: In a study of adolescent girls, school proximity to recreation facilities was associated with PA [ 114 ]. Another study, focused on 12 th graders, found that those who attended schools with five or more physical activity facilities within a 0.75 mile buffer zone around the school were more physically active than those attending schools with fewer than 5 nearby physical activity facilities [ 115 ].…”
Section: Resultsmentioning
confidence: 99%
“…6,44,60,61 Some evidence also suggests that “active transportation” has an alternative meaning in rural settings that have greater geographic dispersion; where active transportation often means availability of transportation to get to a PA resource location. Recent analysis of national data from 2000 has shown that rural census tracts, relative to metropolitan ones, have less high-intensity development, developed open spaces (e.g., parks, trails), intersection density, and street segment density, and have longer median block lengths; all suggesting lower walkability in rural areas.…”
Section: Behavior Settingsmentioning
confidence: 99%
“…As research suggests that students accumulate a substantial portion of their PA in the neighbourhood's surrounding schools (Asanin-Dean and Elliott 2011;Trilk et al 2011), the built environment features within this area may also help to explain the variability in student PA across schools. Results of three multilevel studies investigating built environment features within the school neighbourhood reveal few associations with student PA (Cradock et al 2009;Deforche et al 2010;Nichol et al 2010) with some exceptions including destinations of interest to youth (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Five kilometres may be too large a distance to expect students to travel to access neighbourhood PA resources. Indeed, recent PA research suggests that a buffer of 1 km is considered to be an easy walking distance for adolescents (Colabianchi et al 2007, Trilk et al 2011. Learning more about the associations between student PA and features of the built environment within 1 km of schools may provide important insight for school-based PA interventions targeting adolescents.…”
Section: Introductionmentioning
confidence: 99%